Enhancing Selection Effectiveness of KIP Fund Recipients Using SAW Method - Hadiningrat, Jaya Saputra; Daniati , Erna; Wardani, Anita Sari (International Journal of Informatics and Computation, 2025)
The selection process for recipients of the Indonesia Smart Card (KIP) fund at Nusantara PGRI University had been conducted manually and inefficiently. Thus, this paper focuses on developing a model that can effectively select potential recipients based on predetermined criteria. The study aimed to create a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to streamline the selection process. The SAW method was chosen due to its ability to handle multi-attribute criteria through weighting and matrix normalization. Data were collected through interviews, observations, and literature reviews, using 12 assessments. The system successfully ranked candidates, with A2 identified as the top priority (score: 0.7278), and the calculation results were validated through manual testing using Excel, confirming the system’s consistency.